2007
DOI: 10.1107/s0021889807000878
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron X-ray scattering studies on the structural evolution of microbial poly(3-hydroxybutyrate)

Abstract: The crystallization behavior of microbially synthesized poly(3-hydroxybutyrate) was studied in detail using time-resolved small-angle X-ray scattering. This polyester was found to undergo primary crystallization as well as secondary crystallization. In the primary crystallization, the thicknesses of the lamellar crystals were sensitive to the crystallization temperature, but no thickening was observed throughout the entire crystallization at a given temperature. The thickness of the lamellar crystals in the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Values established for l c and l a found in the literature for PHB films were 12-47 Å and 8-14 Å respectively 16 ; 5.79-8.87 nm and 2.76-3.75 nm respectively 27 ; 28.5 Å and 26.9 Å respectively 28 . As can be noticed, the lamellar crystals thickness was always larger than that of the amorphous layers, as we have also found.…”
Section: What Changes Inmentioning
confidence: 57%
“…Values established for l c and l a found in the literature for PHB films were 12-47 Å and 8-14 Å respectively 16 ; 5.79-8.87 nm and 2.76-3.75 nm respectively 27 ; 28.5 Å and 26.9 Å respectively 28 . As can be noticed, the lamellar crystals thickness was always larger than that of the amorphous layers, as we have also found.…”
Section: What Changes Inmentioning
confidence: 57%
“…where ðdAE=dÞ silica is the absolute scattering cross section of silica, and I i , %T i and t i represent the scattering intensity, transmission and thickness of the i component, respectively. In addition, SAXS experiments were conducted at the SAXS beamlines (4C1 and 4C2) (Bolze et al, 2002;Lee et al, 2004Lee et al, , 2008Jang et al, 2006;Choi et al, 2007;Jin et al, 2007;Kim et al, 2007Kim et al, , 2008Jin, Park et al, 2008;Heo et al, 2007;Heo, Yoon, Jin, Kim et al, 2008;Heo, Yoon, Jin, Sato et al, 2008;Yoon et al, 2007;Yoon, Jung et al, 2008;Yoon, Kim et al, 2008) of Pohang Accelerator Laboratory (Ree & Ko, 2005) at Pohang University of Science and Technology in Korea. SAXS measurements were carried out at room temperature for a series of octene-mLLDPE(D)/ LDPE(H) blend samples by using a two-dimensional CCD detector (Princeton Instruments Inc., USA) consisting of 1152 Â 1242 pixels.…”
Section: Sample Preparationmentioning
confidence: 99%
“…In addition to the crystallographic parameters and interchain interaction in the crystal state, crystallization behavior has also been investigated for PHBH as well as P3HB homopolymer. Isothermal crystallization behavior from the melt has been investigated for P3HB homopolymer by IR spectroscopy, polarized optical microscopy (POM), differential scanning calorimetry (DSC), X-ray scattering measurements, and so on. In melt-isothermal crystallization experiments for polymers, it is necessary to conduct rapid cooling, so-called temperature-jump ( T -jump), from the melt to avoid any crystallization in the cooling process. Hu et al reported the melt-isothermal crystallization kinetics of P3HB homopolymer by near-IR (NIR) and IR spectroscopy and principal component analysis (PCA).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that secondary crystallization occurred favorably in the later stage of crystallization in competition with the continuous primary crystallization. In comparison with the primarily formed lamellar crystals, the secondary crystals had short-range-ordered structures of a smaller size and a broader size distribution . The entire image of isothermal crystallization behavior from the melt has been proposed for P3HB homopolymer as follows: In the melt state, P3HB chains form a random conformation having the intrachain and interchain C–H···OC hydrogen bond.…”
Section: Introductionmentioning
confidence: 99%